Identification of the Molecular Basis of Nanocurcumin-Induced Telocyte Preservation within the Colon of Ulcerative Colitis Rat Model - Eetmad A. Arafat; Rehab Elsayed Marzouk; Sally Abdallah Mostafa; Walaa H. E. Hamed (Mediators of Inflammation)
Background. Telocytes (TCs) are a distinct type of interstitial cells that play a vital role in the pathogenesis of ulcerative colitis and colonic tissue hemostasis. The aim of this study was to examine the effect of nanocurcumin (NC) on the morphometric and immunohistochemical characterization of TCs in the ulcerative colitis (UC) rat model. Methods. Forty rats were randomly divided into control, NC, UC, and UC+NC groups. At the end of the experiment, the colon was dissected and prepared for histopathological and immunohistochemical assessment. Tissue homogenates were prepared for real-time PCR assessment of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and transforming growth factor-beta (TGF-β) gene expression. Our results revealed extensive mucosal damage with inflammatory cell infiltration, significant reduction of CD34, and vimentin immunostained TCs in the colon of the UC group with significant elevation of expression of IL-6, TNF-α, and TGF-β. The UC+NC-treated group revealed significant elevation of TC count compared to the UC group besides, a significant reduction of the three gene expression. Conclusion. NC successfully targeted the colonic tissue, improved the mucosal lesion, preserve TCs distribution, and count through its anti-inflammatory and fibrinolytic properties.